Build Your Own .NET Language and Compiler - Nigles, Edward G. (Apress, 2012)
Dijkstra didn'tplay for the Chicago Cubs baseball club, to my knowledge, nor did he play for the Arsenal, Chelsea, Antwerp or Eindhoven football organizations (nor did Dylan, but you knew that). Instead, Edsger Wybe Dijkstra was a founding computer scientist who was involved in the early Algol language and either invented or reported the invention of structured programming.